Proposed Reference Model for Guiding Teachers to Perform Ward Round Teaching - Luís Alberto Corona Martínez (Medisur)
Ward round teaching is an essential professional medical activity as an organizational form of teaching in undergraduate medical education. Its great importance for shaping a professional "personality" is well recognized by the faculty; as well as its extremely complex implementation and development of the necessary skills. The problem to be solved in this paper is related to the need to help younger clinical teachers in undergraduate medical education to develop the skills to conduct ward round teaching; which would be achieved through appropriate guidance on how to perform this activity. Based on this, the teaching staff in the Department of Clinical Sciences of the Dr. Raúl Dorticós Torrado Faculty of Medical Sciences in Cienfuegos has designed a model or representation of ward round teaching to be used as a guide. The main results include the development of a model with two variants, according to the care provided to a recently admitted patient or an already known patient; and the definition of conditions, both in practical and educational areas, which should be considered for the proper implementation of the activity. The model is not a complete representation of the ward round teaching, thus the proposal is open to review and improvement; and its use is based on its adaptation to the particularities of the different disciplines and learning scenarios.